Perlindungan Hukum Internasional terhadap Pelaksanaan Adopsi Anak Antar Negara - Wardah Wardah (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: The child protection, particularly in intercountry adoptions, should be increased considerably. It is needed a government to government intervention to impede and discontinue the illegal intercountry adoption practices. There are systemic gaps in the current intercountry adoption systems, for instance it happens in some poor countries and developing countries. This article concludes that contracting countries involving in the intercountry adoption practice should ratify the Hague Convention, and at the same time poor country should enters into a bilateral agreement with some certain developed countries, such as the USA and France, in order to protect children from abduction of, traffic in or sale of children. International Law Protection Towards the Children Adoption